Increasing knowledge and skills in processing orange peel waste into eco enzymes for senior high school students - Wilda Amananti; Aldi Budi Riyanta; Inur Tivani; S. Susiyarti (Journal of Community Service and Empowerment, 2024)
Environmental education and awareness of sustainability are becoming a major focus in educational curricula around the world. This article discusses an innovative approach to environmental learning for high school students through the creation of ecoenzymes. Ecoenzym, is a mixture of fermented organic materials that has the ability to clean and recycle organic waste, as well as improve soil and water quality. The results of ecoenzyme training activities for high school students based on the pretest and posttest results are that the training has a positive impact on students' understanding of ecoenzymes and their ability to apply them in practice. The posttest results showed a significant increase in students' knowledge and skills after participating in the training, compared to the pretest results. In this training, students are given a deeper understanding of ecoenzymes. Students get the opportunity to participate in practical activities involving the use of ecoenzymes, which can increase their understanding of the concept. In conclusion, ecoenzyme training is an effective strategy in increasing the knowledge and skills of high school students in this regard. This suggests that practical, hands-on approaches such as this training can be an effective method in educating students about complex scientific concepts such as ecoenzymes.